Treatment of Hip and Knee Osteonecrosis: A Presentation of Three Cases and Evidence-based Algorithm - Elle, Commerce,; Monti, Khatod, (Medical Science: Trends and Innovations Vol. 8, 2025)
Osteonecrosis of the hip and knee presents challenging cases for the orthopaedic surgeon. ON of the hip and knee can be a source of severe morbidity for affected individuals. Although several risk factors and explanations for the pathogenesis of ON have been recognized, there exists little consensus in the literature as to the appropriate clinical management. Here are the cases of three patients who were treated at the institution and a treatment algorithm for hip and knee osteonecrosis was conducted. The cases represent pre- and post-collapse lesions of the hip and knee. Current evidence is reviewed and an algorithm for both hip and knee ON is presented. Core decompression may be used in small, pre-collapse areas of osteonecrosis especially if the involved bone has minimal involvement of the weight-bearing surface. Arthroplasty has proven to be an excellent option for patients with osteonecrosis and debilitating pain and function. This study has found that one can achieve excellent results with arthroplasty in the setting of osteonecrosis.